Marisa Marthari, Colin Renfrew and Michael J. Boyd (eds). Beyond the Cyclades. Early Cycladic sculpture in context from mainland Greece, the north and east Aegean. pp. 328, 265 b/w ills, 8 tables. 2019. Oxford: Oxbow Books. ISBN 9-781-58925-063-2, hardbac - Dickinson, Oliver (Journal of Greek Archaeology, 2020)
This is the third in a series produced to publish a sequence of symposia in Athens that started in 2014 with ‘Cycladic Sculpture in Context’. Such ‘sculpture’ consists in all cases of figurines (rarely very large, although a few are more like statuettes or even, very rarely, something like life size). These figurines are almost entirely of stone, generally white marble, and belong to a well-known tradition that had its home in the EBA (Early Bronze Age) Cyclades, of which the ‘folded-arm figurine’ (FAF) is an internationally recognised type. Until recently, a large proportion of this class of material was represented by holdings in museum and private collections, generally the results of looting and often lacking even a claimed provenance. However, the momentous discoveries in excavations on Keros, a small island south-east of Naxos that was an early reported source of such material, have revolutionised our view of the whole class and the part they played in Cycladic EB culture. The lively debate on their interpretation and significance that followed the new discoveries led to the series of symposia in Athens, that was deliberately focused on the proportion of the material that could be given an archaeological context or at least a secure provenance. Previously published volumes have concerned the finds with provenances in the Cyclades and in Crete; this volume incorporates examples from the Greek mainland, other Aegean islands – mainly the Dodecanese, but there are examples from Skyros and Lesbos – and a solitary find from Miletus, seemingly ‘recontextualised’ in a phase succeeding the EBA.